Requirement of ClpX for CtsR dissociation from its operator elements upon heat stress in Bacillus subtilis - Harms, Marco; Kaden, Chelsea; Busch, Larissa M.; Dhople, Vishnu M.; Gerth, Ulf; Gesell Salazar, Manuela; Michalik, Stephan; Zhatarova, Zhanetta; Völker, Uwe; Reder, Alexander (Frontiers in Microbiology, 2025)
A sudden increase in temperature triggers Bacillus subtilis to activate expression of stress-specific heat shock proteins of the CtsR (class three stress gene repressor) regulon to withstand the adverse conditions. Key members of this regulon, such as ATPases, proteolytic subunits and their adaptors, which can assemble to the functional Clp protease system, perform crucial roles in maintaining cellular proteostasis, while their transcription is repressed by CtsR during vegetative growth. Upon heat shock, a conformational change in a thermosensing glycine-rich loop causes CtsR to detach from its DNA operators, enabling the transcriptional activation of the regulon. Novel data from a clpX-deficient strain demonstrated that in addition, the presence of the ATPase ClpX is essential for the CtsR dissociation from its DNA binding site. To further elucidate this role of ClpX, we constructed a conditional clpX strain, in which clpX induction is decoupled from its native transcriptional control. This conditional expression system mimicked a clpX-deficient phenotype under non-inducing conditions and restored the wild-type phenotype upon induction. Our results indicate that the full induction of the CtsR regulon, particularly clpE, requires both heat and the presence of ClpX, thereby extending the current model for the transcriptional activation of genes repressed by CtsR.